Pengaruh Terapi Dzikir Terhadap Kadar Glukosa Darah Pasien Diabetes Melitus Tipe 2 - Sitti Fatimah M. Arsad; Erna Rochmawati; Arianti Arianti (Wiraraja Medika : Jurnal Kesehatan, 2020)
Abstract Diabetes mellitus is a chronic disease with metabolic disorders in the form of increased blood glucose levels caused by disruption of insulin secretion or insulin efficacy. Management of diabetes can be done by pharmacology or nonphamacology therapy. One of the nonpharmacological therapies is dhikr therapy. The study design used quasy experiment with the control group pre-post test design. The collected samples are 40 diabetes patients with simple random technique. The research sample was divided into 2 groups,control and intervention group, each of which was 20 respondents. Data analysis uses independent t-test. The results showed that dzikir therapy of sentences thayibah, asmaul husna and prayers performed every day for 2 weeks could significantly reduce patients blood glucose levels (p = 0.000) or p <0.05. Key Words : Dhikr Therapy, Blood Glucose Level, Type 2 Diabetes Melitus